LG in India (B) : product strategies in an emerging economy - Salwan, Prashant (London : NeilsonJournals Publishing, 2011)
Entering an emerging economy can provide many opportunities as well as challenges. The external forces, in particular cultural and demographic, are quite different compared to those of a developed economy or the multinational company's home market. MNEs typically use strategies such as product development, adaptation, and standardization to tackle competition in emerging economies. LG mapped its "go to market capabilities" and product strengths and crafted its strategies for growth in India along these lines. The three product level strategies (core product, product attributes, and support services) are investigated in detail.
Originally Published InSalwan, P. (2011). LG in India (B): Product strategies in an emerging economy. Journal of International Business Education, 6(1), 59-76. JIBE6-0CS2.
Description based on XML content.
Keywords: elektronické knihy; electronic books; LG Cho?nja (Korea) -- Management -- Case studies; International business enterprises -- Management -- Case studies; Electronic industries -- India -- Case studies; Electronic industries -- Korea -- Case studies